2023
DOI: 10.14336/ad.2022.1127
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota is an Impact Factor based on the Brain-Gut Axis to Alzheimer’s Disease: A Systematic Review

Abstract: Alzheimer's disease (AD) is a degenerative disease of the central nervous system. The pathogenesis of AD has been explained using cholinergic, β-amyloid toxicity, tau protein hyperphosphorylation, and oxidative stress theories. However, an effective treatment method has not been developed. In recent years, with the discovery of the brain-gut axis (BGA) and breakthroughs made in Parkinson's disease, depression, autism, and other diseases, BGA has become a hotspot in AD research. Several studies have shown that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 155 publications
0
4
0
Order By: Relevance
“…The study suggested that LF82 can induce enteritis-like manifestations and cognitive impairment through escape of gut metabolites, causing transcriptional changes in the brain. This study expands our understanding of the link between gut microbiota and neurological disorders, a field of increasing interest ( Cryan et al., 2019 ; Zou et al., 2023 ).…”
mentioning
confidence: 69%
“…The study suggested that LF82 can induce enteritis-like manifestations and cognitive impairment through escape of gut metabolites, causing transcriptional changes in the brain. This study expands our understanding of the link between gut microbiota and neurological disorders, a field of increasing interest ( Cryan et al., 2019 ; Zou et al., 2023 ).…”
mentioning
confidence: 69%
“…Certain microorganisms released LPS, amyloid, and other immunogenic mixtures into the surrounding environment, promoting Aβ accumulation and inflammation, activating the signaling pathway in AD pathogenesis. Bacterial amyloid protein is associated with molecular and cellular adaptation, adhesion stimulation, aggregation, biofilm formation, tissue invasion, bacterial colonization, and pathogen infectivity [73]. Conversely, treatment with Clostridium butyricum improved cog-nitive function in rats, reducing neuronal apoptosis, increasing brain-derived neurotrophic factors, and decreasing pro-inflammatory cytokines [74].…”
Section: Neurological Changes and Dysbiosismentioning
confidence: 99%
“…Alzheimer's disease is a disorder with neurodegenerative nature that progressively weakens the brain, causing memory loss, cognitive decline, and changes in behavior. 135 It is the main disease leading to dementia in older adults and is resulted from the buildup of beta‐amyloid plaques and tau protein tangles in the brain, which result in the death of brain cells and the shrinking of brain tissue. 136 There is no precise etiology for AD, but it appears to be linked to a variety of factors including genetics, environment, and lifestyle.…”
Section: Neuroprotective Effects Of Gemfibrozil On Neurological Disor...mentioning
confidence: 99%